Aplikasi Srikandi sebagai Inovasi dalam Pengelolaan Surat di Kecamatan Mbeliling Kabupaten Manggarai Barat - Camelya Declarita Dapa Ngara; Hendrik Toda; Mariayani O. Rene; Maria M. Lino (Universitas Kristen Indonesia Toraja, 2026)
Digital transformation in public administration has encouraged the adoption of various innovations to improve administrative effectiveness, including the Integrated Dynamic Archival Information System (SRIKANDI). This application was developed to support electronic correspondence and records management within the framework of Electronic-Based Government Systems. This study aims to analyze the implementation of SRIKANDI as an innovation in correspondence management at Mbeliling Subdistrict Office, West Manggarai Regency. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving seven informants selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing. The analysis was guided by the Diffusion of Innovation theory, focusing on the dimensions of relative advantage, compatibility, complexity, trialability, and observability. The findings indicate that SRIKANDI improves administrative efficiency through electronic correspondence management, digital disposition, electronic signatures, and better archive security. The application is generally compatible with organizational needs; however, its utilization remains constrained by limited digital competencies among employees. The implementation process also faces challenges related to unstable internet connectivity and uneven user capacity, resulting in a relatively high level of perceived complexity. Furthermore, application trials prior to full implementation were found to enhance user understanding of system features and procedures, thereby reducing technical barriers and increasing acceptance of the innovation. The study concludes that the successful adoption of SRIKANDI depends on technological benefits, adequate digital infrastructure, and human resource readiness.